2022
DOI: 10.1002/anie.202203692
|View full text |Cite
|
Sign up to set email alerts
|

Decarbonylative Transfer Hydrochlorination of Alkenes and Alkynes Based on a B(C6F5)3‐Initiated Grob Fragmentation

Abstract: Readily available cyclohexa‐2,5‐dien‐1‐ylcarbonyl chloride derivatives are introduced as bench‐stable HCl surrogates for transfer hydrochlorination of terminal and internal alkenes as well as selected alkynes. The stepwise Grob fragmentation of those acyl chlorides into chloride, carbon monoxide, a low‐molecular‐weight arene, and a proton is promoted by B(C6F5)3. This decarbonylative transfer process enables the addition of HCl across C−C double and triple bonds with Markovnikov selectivity at room temperature. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In 2022, Oestreich reported the in situ formation of HCl by Lewis acid-induced Grob fragmentation of acid chloride 92 ( Scheme 15B ) [ 68 ]. The inconvenience of this method is that 92 has to be prepared in two steps, including a Birch reduction ( Scheme 15A ).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, Oestreich reported the in situ formation of HCl by Lewis acid-induced Grob fragmentation of acid chloride 92 ( Scheme 15B ) [ 68 ]. The inconvenience of this method is that 92 has to be prepared in two steps, including a Birch reduction ( Scheme 15A ).…”
Section: Reviewmentioning
confidence: 99%
“…Kropp and co-workers observed that the remaining 2% of the alkene was a mixture of E-and Z-octene (67) (Scheme 10). They also mentioned in a footnote that 2-chlorooctane (41) was contaminated by "some 3-chlorooctane" (68). The formation of regioisomers through hydride or alkyl shifts is a common occurrence in hydrochlorination reactions involving secondary cations (Scheme 10).…”
Section: Reactions With In Situ-generated Hclmentioning
confidence: 99%
“…Developing novel methodologies for functional group transformations has always been an attractive yet challenging research area. In this aspect, functional group exchanges offer new opportunities and have a broadly advantageous impact. Despite the recent progress, the field of functional group exchange reactions is still in its infancy. For example, most of the known processes were based on the transformation of multiple bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrochlorination of an unsaturated triple bond is a useful method for providing alkenyl chloride compounds, which have emerged as versatile building blocks for divergent molecular syntheses and widely exist in natural products and bioactive molecules . Meanwhile, alkenyl chloride could be conveniently transformed into different carbon–carbon and carbon–heteroatom bonds. , However, the methods for accessing alkenyl chloride remain quite limited . Recently, Engle reported Pd-catalyzed directedanti-hydrochlorination of alkynes with high selectivity (Figure B).…”
mentioning
confidence: 99%